Global trends and performances in diabetic retinopathy studies: A bibliometric analysis - Xiao, Huan; Tang, Jinfan; Zhang, Feng; Liu, Luping; Zhou, Jing; Chen, Meiqi; Li, Mengyue; Wu, Xiaoxiao; Nie, Yingying; Duan, Junguo (Frontiers in Public Health, 2023)
Objective: To identify and evaluate the global trends in diabetic retinopathy (DR) research of the past century, and visualize the focus and frontiers by bibliometric analysis. Methods: Literature about DR published from the establishment of the Web of Science (WOS) to November 1, 2022, was retrieved. Qualitative and quantitative analysis was conducted based on the database. This paper analyzed the annual publication count, prolific countries, institutions, journals, and the top 10 most cited literature. The results were presented through descriptive statistics. VOSviewer1.6.17 was used to demonstrate the collaboration networks of countries and high-frequency keywords. CiteSpace5.5.R2 was used to visualize the keywords’ timeline and burst keywords. Results: A total of 10709 references were analyzed, and the number of publications continually increased over the investigated period. America had the greatest influence, due to the highest h-index and citation frequency. China was the largest productive country, with 3,168 articles published. The most productive institution was the University of London. The top three productive journals were also from America, and Investigative Ophthalmology Visual Science had the highest number of publications. The Gulshan V, etc. 's (2016) article (co-citation counts,2897) was the representative and symbolic reference. The main research topics in this area were incidence, pathogenesis, treatment, and artificial intelligence (AI). Deep learning, models, biomarkers, and optical coherence tomography angiography (OCTA) of DR were frontier hotspots. Conclusions: Bibliometrics analysis in this study could help scholars comprehend global trends of DR research frontiers better. Four main research directions and three research frontiers were extracted from the numerous DR -related literature. As the prevalence of DR increases, developing AI technology and telemedicine to balance the population of doctors and patients is a potential research hotspot.